CYTOGENETIC BIOMONITORING AND IMMUNOCYTOCHEMICAL STUDIES ON CAR SPRAY PAINTERS IN ENUGU METROPOLIS, ENUGU STATE, NIGERIA: Cytogenetic biomonitoring of workers exposed to Car paint - ANULIKA ONYEMELUKWE; PETER ACHUKWU; NKIRUKA AZUBUIKE; UZOAMAKA MADUAKOR; OKECHUKWU ONWUKWE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study assessed the cytogenetic damage associated with occupational exposure to paints by evaluating exfoliated buccal epithelial cells from car spray painters in Enugu metropolis using some biological markers. Methods: A total of 352 apparently healthy males, comprising 200 car spray painters and a control group of 152 individuals, participated in the study. Buccal smears were obtained from each participant and were stained using hematoxylin and eosin technique. A total of 1000 cells per individual were scored under light microscopy to determine the frequencies of micronuclei (MN) and binucleate cells (BNC). Structured questionnaires were used to obtain relevant participant information. Expression patterns of Ki-67and p53 genes on the buccal cells were determined by immunocytochemical methods. Results: Car spray painters had significantly increased frequencies of MN and BNC (*p<0.05) when compared to the control subjects. Paint sprayers aged over 35 years had higher buccal cell MN frequency when compared to those <25 years. Furthermore, car spray painters who have worked for ≥15 years had higher frequencies of MN when compared to those who had worked for <5 years (*p<0.05). Smoking and alcohol consumption increased the MN frequency of the car spray painters (*p<0.05). There was no expression of p53 and Ki-67 genes in the buccal cells of both control and exposed subjects. Conclusion: Car spray painters in Enugu metropolis may be occupationally exposed to substances capable of inducing genotoxic changes which manifested as increased frequency of MN in their buccal cells.